Polymorphism of Sakini Chicken Population From Different Locations/Altitudes of Nepal Using Randomly Amplified Polymorphic Dna Markers (SAARC Journal of Agriculture, 2021)
A study was conducted to evaluate genetic polymorphism in three Sakini chicken populations using random amplification of polymorphic DNA (RAPD) with seven highly polymorphic primers. All populations showed polymorphism with these primers that generates 59 different bands with an average of 8.4 bands per primer with 78.6% polymorphism nature. Primer OPA-16 produced the highest number of polymorphism bands 47 % and the lowest number of bands was produced by the OPA-05 primer 24 %. Differences for genetic distance (D) among populations were significant (P